From Sumatra 2004 to Tohoku‐Oki 2011: The systematic GPS detection of the ionospheric signature induced by tsunamigenic earthquakes. Issue 6 (17th June 2013) - Occhipinti, Giovanni; Rolland, Lucie; Lognonné, Philippe; Watada, Shingo
Abstract : [1] The recent tsunamigenic earthquake in Tohoku (11 March 2011) strongly affirms, one more time after the Sumatra event (26 December 2004), the necessity to open new paradigms in oceanic monitoring. Detection of ionospheric anomalies following the Sumatra tsunami demonstrated that ionosphere is sensitive to the tsunami propagation. Observations supported by modeling proved that tsunamigenic ionospheric anomalies are deterministic and reproducible by numerical modeling via the ocean/neutral‐atmosphere/ionosphere coupling mechanism. In essence, tsunami induces internal gravity waves propagating within the neutral atmosphere and detectable in the ionosphere. Most of the ionospheric anomalies produced by tsunamis were observed in the far field where the tsunami signature in the ionosphere is clearly identifiable. In this work, we highlight the early signature in the ionosphere produced by tsunamigenic earthquakes and observed by GPS, measuring the total electron content, close to the epicenter. We focus on the first hour after the seismic rupture. We demonstrate that acoustic‐gravity waves generated at the epicenter by the direct vertical displacement of the source rupture and the gravity wave coupled with the tsunami can be discriminated with theoretical support. We illustrate the systematic nature of those perturbations showing several observations: nominally the ionospheric perturbation following the tsunamigenic earthquakes in Sumatra on 26 December 2004 and 12 September 2007; in Chile on 14 November 2007; in Samoa on 29 September 2009; and the recent catastrophic Tohoku‐Oki event on 11 March 2011. Based on the analytical description, we provide tracks for further modeling efforts and clues for the interpretation of complex—and thus often misleading—observations. The routine detection of the early ionospheric anomalies following the rupture highlights the role of ionospheric sounding in the future ocean monitoring and tsunami detection. Key Points: Systematic first hours ionospheric perturbations for 5 events from 2004 to 2011 Separation of the source signature vs the tsunami signature in the ionosphere Fully explication of the tsunami oceanic/ionospheric observation delay